PENILAIAN PROGRAM DIPLOMA TATABUSANA TERHADAP PEMBENTUKAN SIKAP DAN PEMIKIRAN BERWIRAUSAHA ALUMNI - Ernawati PhD; Nor Aishah Buang (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
This study attempts to assess conformity diploma attitude entrepreneurs on the establishment of the alumni fashion entrepreneurship of engineering faculty state university the ( TB FT UNP ) .This research use the model input assessment , processing and products (Cipp) by stufflebeam et al .1971 .The population in research is alumni diploma TB FT UNP about 218 people. All made the sample population. An analysis of data using descriptive statistics .error research instruments measured by the correlation items and referral experts , while index standard deviation value cronbach alpha that reflects the between 0.70 to 0.97 . May be trustworthy item is high and acceptable .The results of the curriculum , not appropriate to form attitude entrepreneurship score of min 3.33 and standard deviation 0.92 but based on the establishment of the thought entrepreneurship min 3.91 and standard deviation 0.91 . Academic and climate